Ceramic brake pad for new energy automobile and preparation method of ceramic brake pad

By using specific ratios of ceramic materials, resins, staple fibers and fillers in ceramic brake pads, and using intensive refining, ball milling and pressure forming processes, the shortcomings of ceramic brake pads in wear and heat resistance are solved, and the problem of ceramic brake pads is achieved. More efficient and economical ceramic brake pad preparation, suitable for the braking system of new energy vehicles.

CN119508399APending Publication Date: 2025-02-25JIANGSU FANGYI AUTOPART MANUFACTURE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411718974.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

While maintaining a high coefficient of friction, existing ceramic brake pads are difficult to take into account good wear resistance and heat resistance. The preparation process is complex and cost control is difficult, which limits its wide application in the field of new energy vehicles.

Method used

The friction material layer including ceramic materials, resins, staple fibers and fillers is used to improve the wear and heat resistance of the brake pads through selected materials and specific fillers ratios, and the uniform distribution of materials and structural stability are ensured by using dense refining, ball milling and pressure forming processes.

Benefits of technology

It has achieved wear resistance and heat resistance of ceramic brake pads, extended service life, reduced maintenance costs, and improved the energy efficiency and handling performance of new energy vehicles through lightweight design.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119508399A_ABST
    Figure CN119508399A_ABST
Patent Text Reader

Abstract

The invention provides a ceramic brake pad for a new energy automobile and a preparation method of the ceramic brake pad. The ceramic brake pad comprises a friction material layer and a lining plate. The friction material layer is made of ceramic materials, covers the lining plate and is connected with the lining plate through the through holes. The through hole is filled with a vulcanization layer. The filler comprises diatomite, mica, ceramic fiber and the like, and the short fiber comprises aramid fiber, nylon fiber and the like. The friction material layer further includes a binder. According to the invention, excellent wear resistance and thermal stability can be realized, and a high-performance braking solution is provided for a new energy automobile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy vehicle braking systems, and more specifically, to a ceramic brake pad for a new energy vehicle and a preparation method thereof. Background Art

[0002] Existing brake pad technology mainly uses metal or semi-metal composite materials, which are prone to failure at high temperatures and generate large noise and dust pollution during braking. In addition, metal brake pads are heavy, which is not conducive to the lightweight design of new energy vehicles. Against the background of increasing requirements for environmental protection, energy saving and performance of new energy vehicles, traditional brake pad materials and designs have been unable to meet market demand. Ceramic brake pads, as a new type of material, are considered to be an ideal choice to replace traditional brake pads due to their excellent wear resistance, high temperature resistance and lightweight properties. However, the existing ceramic brake pads have problems such as inaccurate material ratios, complex molding processes, and high costs during the preparation process, and in actual applications, their friction performance and heat resistance need to be further improved.

[0003] In the process of implementing the embodiments of the present invention, the inventors found that there are at least the following problems or defects in the prior art: it is difficult for existing ceramic brake pads to achieve both good wear resistance and heat resistance while maintaining a high friction coefficient; in addition, the preparation process is complicated and cost control is difficult, which limits their widespread application in the field of new energy vehicles. Summary of the invention

[0004] The present invention provides a ceramic brake pad for a new energy vehicle and a preparation method thereof.

[0005] In a first aspect of the present invention, a ceramic brake pad for a new energy vehicle is provided, comprising: A friction material layer and a lining plate, wherein the friction material layer is covered on the lining plate, a through hole is provided on the lining plate, a circular hole is provided on the friction material layer, the circular hole is connected with the through hole, the through hole is filled with a vulcanized layer, the vulcanized layer is located in the circular hole, the friction material layer is made of a ceramic material, the ceramic material includes a resin, the resin is cured by one or more of polyetheretherketone, diphenyl sulfone, polyphenylene ether, polysulfone, polyimide and a curing agent, the components of the friction material layer include a filler, the filler includes one or more of diatomaceous earth, mica, ceramic fiber, carbon fiber, and graphite, the friction material layer also includes one or more of a binder selected from phenolic resin, acrylate or carboxymethyl cellulose, the components of the wear-resistant material include short fibers, the short fibers include one or more of aramid fibers, nylon fibers, carbon fibers, and glass fibers.

[0006] Furthermore, the filler is composed of diatomaceous earth, mica and ceramic fiber, and in terms of mass percentage, the diatomaceous earth: mica: ceramic fiber = (1-6): (1-3): (1-2).

[0007] Furthermore, the short fibers are composed of nylon fibers and glass fibers, and in the short fibers, by mass percentage, nylon fibers: glass fibers = (2-5): (2-5).

[0008] Furthermore, in the ceramic brake pad for new energy vehicles, the friction material layer has the following composition by mass percentage: ceramic material: resin: short fiber: filler = (12-33): (30-56): (3-9): (1-4).

[0009] Furthermore, in the ceramic brake pad for new energy vehicles, the resin is composed of the following components by mass percentage: polyetheretherketone: (80-90)% diphenyl sulfone: (5-10)% polyphenylene ether: (10-20)%.

[0010] Furthermore, the curing agent in the friction material component is composed of epoxy resin, polyether amine and bisphenol A epoxy resin curing agent, the structural formula of the polyether amine is: H2N-(CH2CHRCHR)n-NH2, and based on the mass percentage of the curing agent, the added amount of the epoxy resin is 5-10%, the added amount of the polyether amine is 20-30%, and the added amount of the bisphenol A epoxy resin curing agent is 15-35%. The ceramic fiber in the filler is composed of any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber, and silicon carbide fiber.

[0011] Furthermore, the short fibers are glass fibers, the glass fibers are chopped glass fibers, and the length of the glass fibers is 0.20-0.8 mm.

[0012] Furthermore, the number of the through holes is at least three, the three through holes are distributed on the circumference of the inner layer of the lining plate, and the angles between adjacent through holes are equal. The distance between adjacent through holes is 10-12 mm, the diameter of the through hole is 2-4 mm, and the depth of the through hole is 80-90% of the thickness of the lining plate.

[0013] In a second aspect of the present invention, a method for preparing a ceramic brake pad for a new energy vehicle is provided, comprising: S1: Weigh the raw materials in the above mass percentage or weight, add the resin into a mixer for mixing, the mixing temperature is 150-240°C, the mixing time is 5-30min, then add short fibers, continue mixing for 5-20min, then add the curing agent, increase the temperature to 250-350°C, continue mixing for 8-30min, then perform vacuum impurity removal, reduce the temperature to 180-200°C, mix for 5-10min, and finally discharge the materials to obtain a resin mixture A; S2: adding the phenolic resin into a ball mill for ball milling for 10-30 min to obtain a phenolic resin mixture B; S3: placing the resin mixture A into a friction tablet press for pressing into a block to obtain a ceramic material block, and then curing the block ceramic material block at a curing temperature of 200-270° C. and a curing time of 2-5 hours; S4: placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5: respectively placing the short fibers and the filler into a jet mill for pulverization pretreatment, and then adding the phenolic resin mixture B obtained in step S2 to the filler, stirring in a mixer at a stirring temperature of 120-150° C. for a stirring time of 10-30 min to obtain a filler mixture; S6: placing the phenolic resin mixture B into the mixer, adjusting the temperature of the mixer to 80-120° C., stirring for 30-60 min, and cooling to room temperature after stirring to obtain a mixture B; S7: Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 120-150°C for 4-8h to prepare the friction material, then heat the friction material to 120-150°C to melt it, add the friction material into a molding machine for pressing at a pressure of 10-25MPa for 2-8min, then keep the pressure at a pressure of 2-5Mpa for 2-5min, heat the friction material to 180-220°C, sinter it, and obtain the friction material layer.

[0014] Further, in step S3, the ceramic material block is placed in a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, and the ceramic material block forms a smooth surface on the bottom surface of the mold. A steel back is provided in the mold, and a release agent is coated on the inner surface of the mold. The ceramic material block is fitted with the steel back, and then it is placed in a press for pressure forming. During the pressure forming process, a through hole is opened on the surface of the steel back, and the through hole forms a circular hole on the ceramic material layer. After the pressure forming is completed, it is cooled, and after cooling to room temperature, it is taken out from the mold to obtain the friction material layer, specifically: In step S4, the pressure forming process is as follows: the ceramic material block and the filler mixture are mixed evenly by a mixer, and then placed in a mold and put into a press for a first press forming, the pressure is 25-35MPa, and the pressure holding time is 5-15min; then a second cold press forming is performed, the pressure is 1-2.5MPa, and the pressure holding time is 5-10min; after cooling, the ceramic material block is taken out, and then polished with sandpaper to form a smooth surface on the top and bottom surfaces of the mold; The mold is placed in a press to be molded, the molding pressure is 30-50 MPa, the molding pressure is 2-6 min, and after the molding is completed, it is cooled and taken out from the mold after cooling to room temperature to obtain the friction material layer; In step S6, the sintering temperature is 500-550°C, the sintering time is 5-10 min, and the sintering pressure is 0.1-0.3 MPa.

[0015] Furthermore, in step S5, when the short fibers and the fillers are pre-crushed in an air flow mill, the particle size of the fillers obtained by crushing in the air flow mill is 0.005-100 μm, and the particle size of the short fibers obtained by crushing in the air flow mill is 0.001-60 μm. In the preparation process of the short fibers, the nylon fibers and the glass fibers are sequentially fed into the air flow mill for crushing. The nylon fibers are first crushed into particles in the air flow mill, and then the crushed resin is crushed for a second time in the air flow mill. Finally, the crushed nylon fibers and the crushed glass fibers are input into a mixer for stirring, and the stirring temperature is 120-150°C.

[0016] Furthermore, the curing agent is composed of epoxy resin, polyether amine and bisphenol A epoxy resin curing agent, the structural formula of the polyether amine is H2N-(CH2CHRCHR)n-NH2, the mass percentages of the epoxy resin, polyether amine and bisphenol A epoxy resin curing agent are: the addition amount of the epoxy resin is 5-10%, the addition amount of the polyether amine is 20-30%, and the addition amount of the bisphenol A epoxy resin curing agent is 15-35%, and the ceramic fiber in the filler is composed of any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber, and silicon carbide fiber.

[0017] Furthermore, the filler is composed of diatomaceous earth, mica, and ceramic fiber, and by mass percentage, the diatomaceous earth: mica: ceramic fiber = (1-6): (1-3): (1-2); the short fibers are composed of nylon fiber and glass fiber, and by mass percentage, in the short fibers: nylon fiber: glass fiber = (2-5): (2-5); in the preparation process of the short fibers, nylon fiber is used as raw material and is initially crushed in a jet mill to obtain nylon fiber powder, and then the nylon fiber powder is secondary crushed by a jet mill to obtain the short fibers, and the short fibers are particles of 0.001-60 μm.

[0018] The above embodiments of the present invention have at least the following beneficial effects: the ceramic brake pad for new energy vehicles provided by the present invention can improve the wear resistance and heat resistance of the brake pad through the selected ceramic material and the specific filler ratio, thereby extending the service life of the brake pad and reducing maintenance costs. At the same time, due to the use of lightweight ceramic materials and specific short fiber reinforcement, the brake pad can effectively reduce the weight of the whole vehicle and improve the energy efficiency and handling performance of new energy vehicles.

[0019] In addition, the ceramic brake pad of the present invention adopts precise mixing, ball milling and pressure forming processes during the preparation process, which can ensure the uniform distribution of materials and the stability of the structure, thereby improving the overall performance of the brake pad. This preparation method can also reduce material waste and production costs, making the ceramic brake pad more economical and market competitive in large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the following detailed description with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which: Figure 1 A schematic flow chart of a method for preparing a ceramic brake pad for a new energy vehicle provided in one embodiment of the present invention. DETAILED DESCRIPTION

[0021] The principles and spirit of the present invention will be described below with reference to several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive characteristics and / or steps, can be combined in any way, unless otherwise described, and can be replaced by other equivalent or alternative features with similar purposes, that is, unless otherwise described, each feature is only one embodiment in a series of equivalent or similar features.

[0023] In some embodiments, a ceramic brake pad for new energy vehicles includes a friction material layer and a lining plate, wherein the friction material layer is covered on the lining plate, a through hole is provided on the lining plate, a circular hole is provided on the friction material layer, the circular hole is connected to the through hole, the through hole is filled with a vulcanized layer, the vulcanized layer is located in the circular hole, the friction material layer is made of a ceramic material, the ceramic material includes a resin, the resin is cured by one or more of polyetheretherketone, diphenyl sulfone, polyphenylene ether, polysulfone, polyimide and a curing agent, the components of the friction material layer include a filler, the filler includes one or more of diatomaceous earth, mica, ceramic fiber, carbon fiber, and graphite, the friction material layer also includes one or more binders of phenolic resin, acrylate or carboxymethyl cellulose, the components of the wear-resistant material include short fibers, the short fibers include one or more of aramid fibers, nylon fibers, carbon fibers, and glass fibers.

[0024] It should be noted that this embodiment relates to a ceramic brake pad for new energy vehicles, which includes a friction material layer and a lining plate, and the friction material layer is covered on the lining plate. Here, the friction material layer refers to the layer that constitutes the main friction part of the brake pad, which contacts the wheel to generate braking force; and the lining plate is a structural component that supports the friction material layer. This structural design helps to improve the stability and durability of the brake pad.

[0025] Specifically, the friction material layer is made of ceramic material, and the ceramic material includes resin, and the resin is cured by one or more of polyetheretherketone, diphenylsulfone, polyphenylene oxide, polysulfone, and polyimide with a curing agent. Here, polyetheretherketone is a high-performance engineering plastic, which is famous for its high temperature resistance and wear resistance; diphenylsulfone is a high-temperature resistant material that can improve the thermal stability of the resin; polyphenylene oxide, polysulfone, and polyimide are also high-performance resin materials, which work together to make the friction material layer have excellent mechanical properties and heat resistance. Fillers include one or more of diatomaceous earth, mica, ceramic fiber, carbon fiber, and graphite, and these fillers can improve the wear resistance and thermal conductivity of the friction material layer.

[0026] Preferably, in the components of the friction material layer, the mass ratio of ceramic material, resin, short fiber and filler can be set to (12-33): (30-56): (3-9): (1-4). This ratio can be adjusted according to specific application requirements to achieve the best performance balance. For example, if higher wear resistance is required, the proportion of filler can be appropriately increased; if better flexibility is required, the proportion of resin can be appropriately increased.

[0027] Furthermore, the vulcanized layer is located in the circular hole, which can provide additional wear protection and extend the service life of the brake pad. The specific material of the vulcanized layer can be selected according to actual needs, for example, a rubber material with high wear resistance and good elasticity can be selected.

[0028] In some embodiments, the filler is composed of diatomaceous earth, mica, and ceramic fiber, and by mass percentage, the diatomaceous earth: mica: ceramic fiber = (1-6): (1-3): (1-2).

[0029] It should be noted that the filler of the brake pad mentioned in this embodiment is composed of diatomaceous earth, mica, and ceramic fiber, and the specific ratio range is diatomaceous earth: mica: ceramic fiber = (1-6): (1-3): (1-2). Here, diatomaceous earth is a natural material formed by the deposition of diatom remains, which has good heat insulation and wear resistance; mica is a layered silicate mineral with excellent electrical insulation and heat resistance; ceramic fiber is a refractory material with high temperature stability and low thermal conductivity. The combination of these fillers can improve the friction performance and heat resistance of the brake pad.

[0030] Specifically, the specific parameters of the filler can be adjusted according to the performance requirements of the brake pad. For example, the proportion of diatomaceous earth can vary from 1% to 6%, the proportion of mica can vary from 1% to 3%, and the proportion of ceramic fiber can vary from 1% to 2%. The adjustment of these proportions can be determined according to the actual braking performance and heat resistance requirements. For example, if the wear resistance of the brake pad needs to be improved, the proportion of diatomaceous earth can be appropriately increased; if the heat resistance needs to be improved, the proportion of ceramic fiber can be appropriately increased.

[0031] Preferably, during the preparation of the filler, the particle sizes of diatomaceous earth, mica and ceramic fiber can be controlled within a certain range to ensure the uniformity of the mixture and the performance of the brake pad. For example, the particle size of diatomaceous earth can be controlled between 10 microns and 100 microns, the particle size of mica can be controlled between 5 microns and 50 microns, and the length of the ceramic fiber can be controlled between 0.1 mm and 1 mm.

[0032] Furthermore, the surface of the filler can be specially treated, such as with a silane coupling agent, to improve its bonding with the resin, thereby improving the overall performance of the brake pad. These treatment steps can be adjusted according to specific production conditions and performance requirements.

[0033] In some embodiments, the short fibers are composed of nylon fibers and glass fibers, and in the short fibers, by mass percentage, nylon fibers: glass fibers = (2-5): (2-5).

[0034] It should be noted that the short fibers of the brake pad mentioned in this embodiment are composed of nylon fibers and glass fibers, and the specific ratio range is nylon fiber: glass fiber = (2-5): (2-5). Here, nylon fiber is a synthetic polymer material known for its high strength and wear resistance; glass fiber is a material known for its high tensile strength and heat resistance. This combination of short fibers can enhance the mechanical strength and heat resistance of the brake pad.

[0035] Specifically, the specific parameters of the short fibers can be adjusted according to the performance requirements of the brake pad. For example, the proportion of nylon fibers can vary between 20% and 50%, and the proportion of glass fibers can also vary between 20% and 50%. The adjustment of these proportions can be determined according to the actual braking performance and heat resistance requirements. For example, if the wear resistance of the brake pad needs to be improved, the proportion of nylon fibers can be appropriately increased; if the heat resistance needs to be improved, the proportion of glass fibers can be appropriately increased.

[0036] Preferably, during the preparation of the short fibers, the diameter and length of the nylon fibers and the glass fibers can be controlled within a certain range to ensure the uniformity of the mixture and the performance of the brake pad. For example, the diameter of the nylon fibers can be controlled between 10 microns and 30 microns, and the length can be controlled between 0.2 mm and 1 mm; the diameter of the glass fibers can be controlled between 10 microns and 20 microns, and the length can be controlled between 0.5 mm and 2 mm.

[0037] Furthermore, the short fibers can be surface treated, such as coated with a silane coupling agent, to improve their bonding with the resin, thereby improving the overall performance of the brake pad. These treatment steps can be adjusted according to specific production conditions and performance requirements.

[0038] In some embodiments, in the ceramic brake pad for new energy vehicles, the friction material layer comprises, by mass percentage: ceramic material: resin: short fiber: filler = (12-33): (30-56): (3-9): (1-4).

[0039] It should be noted that the component ratio of the friction material layer mentioned in this embodiment is ceramic material: resin: short fiber: filler = (12-33): (30-56): (3-9): (1-4). This ratio range ensures that the brake pad has good thermal stability and lightweight properties while maintaining the necessary mechanical strength and wear resistance. Here, ceramic material refers to a composite material mixed with a variety of high-performance resins and curing agents, which together provide the brake pad with excellent heat resistance and wear resistance.

[0040] Specifically, the specific parameters of ceramic materials, resins, short fibers and fillers can be adjusted according to the design requirements and application scenarios of the brake pads. For example, the proportion of ceramic materials can be adjusted between 12% and 33% to ensure the performance of the brake pads at high temperatures; the proportion of resins can be adjusted between 30% and 56% to provide sufficient adhesion and flexibility; the proportion of short fibers can be adjusted between 3% and 9% to enhance the mechanical strength of the material; the proportion of fillers can be adjusted between 1% and 4% to improve the friction performance and heat resistance of the material. The adjustment of these proportions can be determined based on actual performance test results and customer needs.

[0041] Preferably, in order to further optimize the performance of the brake pad, the specific composition of the ceramic material and the resin can be refined. For example, the resin in the ceramic material can be mixed with polyetheretherketone, diphenylsulfone and polyphenylene oxide in a specific ratio to achieve optimal heat resistance and mechanical properties. The proportion of polyetheretherketone can be controlled at 80% to 90%, the proportion of diphenylsulfone can be controlled at 5% to 10%, and the proportion of polyphenylene oxide can be controlled at 10% to 20%. Such a ratio can ensure that the resin remains stable at high temperatures while providing sufficient bonding strength.

[0042] Furthermore, the ceramic fiber in the filler can be any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber or silicon carbide fiber, and can be selected according to specific heat resistance and wear resistance requirements.

[0043] In some embodiments, the ceramic brake pad for new energy vehicles, the resin is composed of the following components by mass percentage: polyetheretherketone: (80-90)% diphenyl sulfone: (5-10)% polyphenylene ether: (10-20)%.

[0044] It should be noted that the resin mentioned in this embodiment is composed of polyetheretherketone, diphenylsulfone, and polyphenylene oxide in a specific ratio. Here, polyetheretherketone is a high-performance polymer known for its excellent heat resistance and mechanical strength; diphenylsulfone is a high-temperature resistant engineering plastic that can improve the heat resistance and chemical stability of the resin; and polyphenylene oxide is a plastic with good mechanical properties and electrical insulation. The combination of these resins provides excellent comprehensive performance for the brake pad.

[0045] Specifically, the specific parameters of the resin can be adjusted according to the performance requirements of the brake pad. For example, the proportion of polyetheretherketone can be controlled between 80% and 90% to ensure the heat resistance and mechanical strength of the resin; the proportion of diphenyl sulfone can be controlled between 5% and 10% to improve the heat resistance and chemical stability of the resin; the proportion of polyphenylene ether can be controlled between 10% and 20% to enhance the mechanical properties and electrical insulation of the resin. The adjustment of these proportions can be determined based on the actual performance test results and customer needs.

[0046] Preferably, in order to further optimize the performance of the brake pad, the specific composition and preparation process of the resin can be refined. For example, polyetheretherketone can use common brands on the market, such as Victrex PEEK, which has excellent heat resistance and mechanical properties; diphenyl sulfone can use Xydar, which is a high-temperature resistant engineering plastic that can improve the heat resistance and chemical stability of the resin; polyphenylene ether can use Ultem, which has good mechanical properties and electrical insulation. During the preparation process, these resins can be mixed evenly through processes such as blending and melt extrusion to ensure the consistency and stability of the resin mixture. In addition, appropriate amounts of stabilizers, antioxidants and other additives can be added as needed to further improve the performance of the resin.

[0047] In some embodiments, the curing agent in the friction material component is composed of epoxy resin, polyether amine and bisphenol A epoxy resin curing agent, the structural formula of the polyether amine is: H2N-(CH2CHRCHR)n-NH2, and in terms of the mass percentage of the curing agent, the added amount of the epoxy resin is 5-10%, the added amount of the polyether amine is 20-30%, and the added amount of the bisphenol A epoxy resin curing agent is 15-35%. The ceramic fiber in the filler is composed of any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber, and silicon carbide fiber.

[0048] It should be noted that the curing agent in the friction material composition mentioned in this embodiment is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent. Here, epoxy resin is a thermosetting plastic, which is widely used due to its good bonding performance and mechanical strength; polyetheramine is a multifunctional amine curing agent that can provide fast curing speed and excellent physical properties; bisphenol A epoxy resin curing agent is a commonly used epoxy resin curing agent, which is well-known for its good electrical insulation and chemical resistance. The combination of these curing agents ensures the high performance and reliability of the brake pad material.

[0049] Specifically, the specific parameters of the curing agent can be adjusted according to the performance requirements of the brake pad. For example, the amount of epoxy resin added can be controlled between 5% and 10%, the amount of polyetheramine added can be controlled between 20% and 30%, and the amount of bisphenol A epoxy resin curing agent added can be controlled between 15% and 35%. The adjustment of these proportions can be determined according to the actual curing speed, mechanical properties and heat resistance requirements. The ceramic fiber in the filler can be composed of any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber, and silicon carbide fiber. The selection of these fibers can be determined according to the required heat resistance and mechanical strength.

[0050] Preferably, in order to further optimize the performance of the brake pad, the specific composition and preparation process of the curing agent can be refined. For example, the structural formula of polyetheramine is H2N- (CH2CH(R)CH(R))n- NH2, where R can be hydrogen or alkyl, and n is the number of repeating units. In practical applications, a suitable polyetheramine can be selected according to specific performance requirements.

[0051] Furthermore, the mixing ratio and order of adding the curing agent will also affect the performance of the final product, so it needs to be precisely controlled. During the preparation process, the epoxy resin and polyetheramine can be mixed first, and then the bisphenol A epoxy resin curing agent can be added at a certain temperature to ensure uniform mixing and optimal curing effect. It is also possible to consider using a vacuum system to remove air bubbles in the mixture to improve the density and strength of the brake pad.

[0052] In some embodiments, the short fibers are glass fibers, the glass fibers are chopped glass fibers, and the length of the glass fibers is 0.20-0.8 mm.

[0053] It should be noted that the short fibers mentioned in this embodiment are glass fibers, and it is particularly pointed out that the glass fibers are chopped glass fibers with a length of 0.20-0.8 mm. Here, chopped glass fibers refer to glass fibers that have been processed by a cutting process and are shorter in length. Such fibers are generally used to reinforce plastics or composite materials to improve their mechanical properties. Glass fibers are widely used due to their high strength, corrosion resistance and good electrical insulation.

[0054] Specifically, the specific parameters of the short fibers can be adjusted according to the performance requirements of the brake pad. For example, the length of the glass fiber can be controlled between 0.20 mm and 0.8 mm. This length range is conducive to forming a uniform distribution in the friction material, thereby improving the overall performance of the brake pad. In addition, the diameter of the glass fiber is also an important parameter, which can usually be selected between a few microns and tens of microns to ensure the dispersion and reinforcement effect of the fiber in the resin matrix.

[0055] Preferably, in order to further optimize the performance of the brake pad, the surface treatment and cutting process of the glass fiber can be refined. For example, the glass fiber can be surface treated before cutting, such as coating with a silane coupling agent, to enhance its bonding with the resin matrix. In the cutting process, precise cutting equipment can be used to control the length and shape of the fiber to ensure uniform distribution of the fiber in the friction material.

[0056] Furthermore, it is also possible to consider mixing glass fibers of different lengths to achieve better reinforcement effect and cost-effectiveness. For example, 0.2 mm and 0.5 mm glass fibers can be mixed in a certain ratio to achieve the desired performance balance.

[0057] In some embodiments, the number of the through holes is at least three, the three through holes are distributed on the circumference of the inner layer of the lining plate, and the angles between adjacent through holes are equal. The distance between adjacent through holes is 10-12 mm, the diameter of the through hole is 2-4 mm, and the depth of the through hole is 80-90% of the thickness of the lining plate.

[0058] It should be noted that the number of through holes mentioned in this embodiment is at least three, and these through holes are distributed on the circumference of the inner layer of the lining plate, and the angles between adjacent through holes are equal. Through holes refer to holes that pass through the lining plate, which play a role in heat dissipation and weight reduction in the structure of the brake pad. This design helps to improve the thermal management and structural strength of the brake pad.

[0059] Specifically, the specific parameters of the through holes can be adjusted according to the design of the lining and the performance requirements of the brake pad. For example, the distance between adjacent through holes can be controlled between 10-12mm, which helps to ensure the strength of the lining while allowing sufficient heat dissipation. The diameter of the through holes can be controlled between 2-4mm, which helps to balance the weight and strength of the lining. The depth of the through holes can be 80-90% of the thickness of the lining, which can ensure the functionality of the through holes while maintaining the basic structural strength of the lining.

[0060] Preferably, in order to further optimize the performance and structure of the brake pad, the manufacturing process of the through hole can be refined. For example, the through hole can be accurately processed by a CNC machine tool to ensure the consistency of the position and size of the hole.

[0061] Furthermore, the edges of the through holes can be chamfered or rounded to reduce stress concentration and improve the fatigue life of the lining. As an alternative, different shapes of through holes, such as elliptical or slotted, can be considered to improve heat dissipation or adapt to specific installation requirements. These design and process optimizations can further improve the performance and reliability of brake pads.

[0062] Reference below Figure 1 , Figure 1 The following is a schematic diagram of a method for preparing a ceramic brake pad for a new energy vehicle according to an embodiment of the present invention. Figure 1 As shown, a method 100 for preparing a ceramic brake pad for a new energy vehicle includes: S1: Weigh the raw materials in the above mass percentage or weight, add the resin into a mixer for mixing, the mixing temperature is 150-240°C, the mixing time is 5-30min, then add short fibers, continue mixing for 5-20min, then add the curing agent, increase the temperature to 250-350°C, continue mixing for 8-30min, then perform vacuum impurity removal, reduce the temperature to 180-200°C, mix for 5-10min, and finally discharge the materials to obtain a resin mixture A; S2: adding the phenolic resin into a ball mill for ball milling for 10-30 min to obtain a phenolic resin mixture B; S3: placing the resin mixture A into a friction tablet press for pressing into a block to obtain a ceramic material block, and then curing the block ceramic material block at a curing temperature of 200-270° C. and a curing time of 2-5 hours; S4: placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5: respectively placing the short fibers and the filler into a jet mill for pulverization pretreatment, and then adding the phenolic resin mixture B obtained in step S2 to the filler, stirring in a mixer at a stirring temperature of 120-150° C. for a stirring time of 10-30 min to obtain a filler mixture; S6: placing the phenolic resin mixture B into the mixer, adjusting the temperature of the mixer to 80-120° C., stirring for 30-60 min, and cooling to room temperature after stirring to obtain a mixture B; S7: Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 120-150°C for 4-8h to prepare the friction material, then heat the friction material to 120-150°C to melt it, add the friction material into a molding machine for pressing at a pressure of 10-25MPa for 2-8min, then keep the pressure at a pressure of 2-5Mpa for 2-5min, heat the friction material to 180-220°C, sinter it, and obtain the friction material layer.

[0063] It should be noted that this embodiment relates to a method for preparing a ceramic brake pad for new energy vehicles, including the steps of weighing raw materials, internal mixing, adding short fibers and a curing agent, vacuum impurity removal, and discharging materials to obtain a resin mixture A. Internal mixing refers to the process of heating and mechanically stirring the resin in an internal mixer to ensure that the resin is fully mixed with various additives. This step is crucial to ensure the uniformity and performance of the brake pad material.

[0064] Specifically, the banburying step in the preparation method can be carried out at a temperature of 150-240°C for 5-30 minutes, then short fibers are added and banburying is continued for 5-20 minutes, then a curing agent is added, the temperature is raised to 250-350°C, and banburying is continued for 8-30 minutes, and finally a vacuum impurity removal operation is performed, the temperature is lowered to 180-200°C, banburying is continued for 5-10 minutes, and the material is discharged to obtain a resin mixture A. The settings of these parameters can be adjusted according to specific material properties and production conditions to obtain the best mixing effect and material properties.

[0065] Preferably, in order to further improve the performance of the brake pad material, the resin mixture A can be subjected to more detailed temperature and time control during the mixing process. For example, a lower temperature can be used in the early stage of mixing to avoid premature curing of the material, and then the temperature can be gradually increased after the curing agent is added to promote the curing reaction.

[0066] Furthermore, vacuum cleaning can be performed at a lower temperature to ensure that air and volatile substances in the material are effectively removed, thereby improving the density and strength of the brake pad. As an alternative, different internal mixers or mixing equipment, such as twin-screw extruders, can be considered to adapt to different production scales and material properties. These refined operating steps and alternatives help optimize the production process and improve product consistency and reliability.

[0067] In some embodiments, in step S3, the ceramic material block is placed in a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, and the ceramic material block forms a smooth surface on the bottom surface of the mold. A steel back is provided in the mold, and a release agent is coated on the inner surface of the mold. The ceramic material block is fitted with the steel back, and then it is placed in a press for pressure forming. During the pressure forming process, a through hole is opened on the surface of the steel back, and the through hole forms a circular hole on the ceramic material layer. After the pressure forming is completed, it is cooled and taken out from the mold after cooling to room temperature to obtain the friction material layer, specifically: In step S4, the pressure forming process is: using a mixer to evenly mix the ceramic material block and the filler mixture, and then placing them in a mold and putting them in a press to perform a compression molding, the pressure is 25-35MPa, and the pressure holding time is 5-15min; Then, a secondary cold pressing is performed, the pressure is 1-2.5MPa, and the pressure holding time is 5-10min; after cooling, the mold is taken out, and then sanded with sandpaper to form smooth surfaces on the top and bottom surfaces of the ceramic material block; The mold is placed in a press to be molded, the molding pressure is 30-50 MPa, the molding pressure is 2-6 min, and after the molding is completed, it is cooled and taken out from the mold after cooling to room temperature to obtain the friction material layer; In step S6, the sintering temperature is 500-550°C, the sintering time is 5-10 min, and the sintering pressure is 0.1-0.3 MPa.

[0068] It should be noted that this embodiment describes in detail the process of placing a ceramic material block into a mold for pressure forming, including the steps of primary pressing, secondary cold pressing, cooling and taking out, and polishing the smooth surface. Pressure forming refers to the process of forming a material into a specific shape under a specific pressure, which is crucial to ensuring the precise size and shape of the brake pad.

[0069] Specifically, in the pressure forming process, firstly, a press forming is performed, the pressure is set at 25-35MPa, and the holding time is 5-15 minutes; then a secondary cold press forming is performed, the pressure is set at 1-2.5MPa, and the holding time is 5-10 minutes; then the block is cooled and taken out, and finally sandpaper is used for grinding to form a smooth surface on the top and bottom surfaces of the ceramic material block on the mold. The settings of these parameters can be adjusted according to the characteristics of the material and the required quality of the finished product to ensure the performance and durability of the brake pad.

[0070] Preferably, in order to further improve the quality and production efficiency of the brake pad, the pressure and holding time can be more finely controlled during the pressure forming process. For example, the pressure of the first press forming can be gradually increased to ensure that the material fills the mold evenly; the second cold press forming can be performed at room temperature to reduce the impact of thermal stress on the material.

[0071] Furthermore, the cooling process can adopt rapid cooling technology to shorten the production cycle. When polishing the smooth surface, sandpaper of different grits can be selected to meet different surface roughness requirements. These refined operating steps and optimization measures help improve the production quality and efficiency of brake pads.

[0072] In some embodiments, in step S5, when the short fibers and the fillers are crushed in a gas flow mill for pretreatment, the particle size of the fillers obtained by crushing in the gas flow mill is 0.005-100 μm, and the particle size of the short fibers obtained by crushing in the gas flow mill is 0.001-60 μm. In the preparation process of the short fibers, the nylon fibers and the glass fibers are sequentially fed into the gas flow mill for crushing. The nylon fibers are first crushed into particles in the gas flow mill, and then the crushed resin is crushed for a second time in the gas flow mill. Finally, the crushed nylon fibers and the crushed glass fibers are input into a mixer for stirring, and the stirring temperature is 120-150°C.

[0073] It should be noted that this embodiment involves the process of pulverizing short fibers and fillers in a jet mill for pretreatment, and it is particularly pointed out that the particle size of the filler is 0.005-100 μm, and the particle size of the short fibers is 0.001-60 μm. A jet mill is a device that uses high-speed airflow to pulverize materials into a desired particle size. This technology is widely used in powder preparation, especially in situations where strict control of particle size is required.

[0074] Specifically, when the short fibers and fillers are pre-treated in the air flow mill, the particle size of the fillers can be controlled between 0.005 and 100 microns, and the particle size of the short fibers can be controlled between 0.001 and 60 microns. The settings of these parameters can be adjusted according to the specific requirements of the brake pad material to ensure the uniformity of the mixture and the mechanical properties of the final product. For example, nylon fibers and glass fibers can be fed into the air flow mill in sequence for pulverization, first pulverizing the nylon fibers into particles, then performing secondary pulverization of the resin in the air flow mill, and finally mixing the pulverized nylon fibers with the pulverized glass fibers.

[0075] Preferably, in order to ensure the best performance of the mixture, the pulverization process of nylon fiber and glass fiber can be more carefully controlled. For example, nylon fiber can be first pulverized into larger particles in an air flow mill, and then the resin can be further pulverized into the desired size by adjusting the air flow speed and pulverization time. The pulverization of glass fiber can also be optimized according to its length and diameter to ensure its good dispersion in the mixture.

[0076] Further, as an alternative, other types of pulverizing equipment, such as ball mills or hammer mills, can be considered to adapt to different production scales and material characteristics. These refined operating steps and alternatives help optimize the production process and improve product consistency and reliability.

[0077] In some embodiments, the curing agent is composed of epoxy resin, polyether amine and bisphenol A epoxy resin curing agent, the structural formula of the polyether amine is H2N-(CH2CHRCHR)n-NH2, and the mass percentages of the epoxy resin, polyether amine and bisphenol A epoxy resin curing agent are: the addition amount of the epoxy resin is 5-10%, the addition amount of the polyether amine is 20-30%, and the addition amount of the bisphenol A epoxy resin curing agent is 15-35%, and the ceramic fiber in the filler is composed of any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber, and silicon carbide fiber.

[0078] It should be noted that the present embodiment describes the specific composition and proportion of the curing agent, which includes epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent. Here, the curing agent refers to a chemical substance used to transform the resin from a liquid or semi-solid state to a solid state, which is crucial to ensure the stability and durability of the brake pad material.

[0079] Specifically, the amount of epoxy resin added to the curing agent can be controlled between 5% and 10%, the amount of polyetheramine added can be controlled between 20% and 30%, and the amount of bisphenol A epoxy resin curing agent added can be controlled between 15% and 35%. The setting of these proportions can be adjusted according to the specific performance requirements of the brake pad material to ensure the curing speed, mechanical strength and heat resistance of the material. The structural formula of polyetheramine is H2N- (CH2CH(R)CH(R))n- NH2, where R can be hydrogen or alkyl, and n is the number of repeating units. This structural formula determines the activity of polyetheramine and its reactivity with epoxy resin.

[0080] Preferably, in order to further improve the performance of the brake pad material, the mixing ratio and addition order of the curing agent can be refined. For example, the epoxy resin and polyetheramine can be mixed first, and then the bisphenol A epoxy resin curing agent can be added at a certain temperature to ensure uniform mixing and optimal curing effect.

[0081] Furthermore, the mixing of curing agents can be carried out under vacuum or inert gas environment to prevent oxidation or other side reactions. As an alternative, different types of curing agents, such as isocyanate or anhydride curing agents, can be considered to adapt to different production conditions and performance requirements. These detailed operating steps and alternatives help optimize the production process and improve product consistency and reliability.

[0082] In some embodiments, the filler is composed of diatomaceous earth, mica, and ceramic fiber, and the mass percentage of the diatomaceous earth: mica: ceramic fiber is (1-6): (1-3): (1-2). The short fibers are composed of nylon fibers and glass fibers, and the mass percentage of the short fibers is: nylon fibers: glass fibers is (2-5): (2-5). In the preparation process of the short fibers, nylon fibers are used as raw materials and are initially crushed in a jet mill to obtain nylon fiber powder, and then the nylon fiber powder is secondary crushed by a jet mill to obtain the short fibers, and the short fibers are particles of 0.001-60 μm.

[0083] It should be noted that the filler mentioned in this embodiment is composed of diatomaceous earth, mica, and ceramic fiber, and the short fiber is composed of nylon fiber and glass fiber, and the specific proportion and preparation process are described. Diatomaceous earth is a natural material formed by the deposition of diatom remains, which has good heat insulation and wear resistance; mica is a layered silicate mineral with excellent electrical insulation and heat resistance; ceramic fiber is a refractory material with high temperature stability and low thermal conductivity. The combination of these fillers can improve the friction performance and heat resistance of the brake pad.

[0084] Specifically, the specific parameters of the filler can be adjusted according to the performance requirements of the brake pad. For example, the ratio of diatomaceous earth, mica, and ceramic fiber can be controlled within the mass percentage range of (1-6): (1-3): (1-2), and such a ratio helps to balance the cost and performance of the material. The ratio of nylon fiber to glass fiber in the short fiber can be controlled within the mass percentage range of (2-5): (2-5), and such a ratio helps to balance the strength and flexibility of the fiber. During the preparation process, the nylon fiber can be firstly crushed in a jet mill to obtain nylon fiber powder, and then the nylon fiber powder is secondarily crushed by a jet mill to obtain short fibers, and the particle size of which is controlled within the range of 0.001-60μm.

[0085] Preferably, in order to further optimize the performance and production efficiency of the brake pad, the preparation process of the filler and the short fiber can be refined. For example, the mixing of diatomaceous earth, mica and ceramic fiber can be carried out under specific temperature and humidity conditions to ensure the uniformity and reactivity of the mixture. The pulverization of nylon fiber and glass fiber can be carried out under controlled air flow speed and pulverization time to ensure that the particle size and shape of the fiber meet the requirements.

[0086] Further, as an alternative, different crushing equipment, such as ball mills or hammer mills, can be considered to adapt to different production scales and material properties. These refined operating steps and alternatives help optimize the production process and improve product consistency and reliability. Example 1

[0087] A ceramic brake pad for new energy vehicles is made of the following components: 30 parts of ceramic material, 50 parts of resin, 5 parts of short fibers, and 10 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 180 ° C, the mixing time is 15 minutes, and then add short fibers, continue mixing for 10 minutes, then add a curing agent, raise the temperature to 300 ° C, continue mixing for 20 minutes, then perform a vacuum impurity removal operation, lower the temperature to 190 ° C, mix for 8 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 20 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 230 ° C and a curing time of 3 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 130° C. for 20 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 100 ° C, stirred for 45 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 130°C for 6 hours to prepare the friction material, then heat the friction material to 150°C to melt it, add the friction material into a molding machine for pressing at a pressure of 15MPa for 5 minutes, then keep the pressure at 3Mpa for 3 minutes, heat the friction material to 200°C, sinter it, and obtain the friction material layer.

[0088] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 2:2:1, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:2, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 7:3:5. The ceramic material includes 85% polyetheretherketone, 7% diphenyl sulfone and 8% polyphenylene ether.

[0089] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0090] Reaction conditions: mixing temperature 180-300℃, ball milling time 20 minutes, curing temperature 230℃, curing time 3 hours, pressure molding pressure 15-18MPa, sintering temperature 150-200℃.

[0091] Yield: The theoretical yield is 100%, and the actual yield is 95%.

[0092] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. Example 2

[0093] A ceramic brake pad for new energy vehicles is made of the following components: 28 parts of ceramic material, 52 parts of resin, 7 parts of short fibers, and 15 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 165 ° C, the mixing time is 20 minutes, and then add short fibers, continue mixing for 12 minutes, then add a curing agent, raise the temperature to 280 ° C, continue mixing for 25 minutes, then perform vacuum impurity removal, lower the temperature to 185 ° C, mix for 10 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 25 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 250 ° C and a curing time of 4 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 140° C. for 25 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 110 ° C, stirred for 50 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 140°C for 7 hours to prepare the friction material, then heat the friction material to 150°C to melt it, add the friction material into a molding machine for pressing at a pressure of 18MPa for 6 minutes, then keep the pressure at 4Mpa for 4 minutes, heat the friction material to 210°C, sinter it, and obtain the friction material layer.

[0094] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 4:2:1, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 4:3, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 8:4:6. The ceramic material includes 82% polyetheretherketone, 8% diphenyl sulfone and 10% polyphenylene ether.

[0095] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0096] Reaction conditions: mixing temperature 165-280℃, ball milling time 25 minutes, curing temperature 250℃, curing time 4 hours, pressure molding pressure 18-21MPa, sintering temperature 150-210℃.

[0097] Yield: The theoretical yield is 100%, and the actual yield is 96%.

[0098] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 3

[0099] A ceramic brake pad for new energy vehicles is made of the following components: 25 parts of ceramic material, 50 parts of resin, 6 parts of short fibers, and 15 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials by mass, add the resin into a mixer for mixing, the mixing temperature is 170 ° C, the mixing time is 25 minutes, and then add short fibers, continue mixing for 15 minutes, then add a curing agent, raise the temperature to 285 ° C, continue mixing for 28 minutes, then perform vacuum impurity removal, reduce the temperature to 190 ° C, mix for 12 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 18 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 260 ° C and a curing time of 3.5 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 145° C. for 18 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 115 ° C, stirred for 40 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 145°C for 5 hours to prepare the friction material, then heat the friction material to 155°C to melt it, add the friction material into a molding machine for pressing at a pressure of 12MPa for 3 minutes, then keep the pressure at 4Mpa for 3 minutes, heat the friction material to 205°C, sinter it, and obtain the friction material layer.

[0100] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 3:2:1, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:4, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 6:5:7. The ceramic material includes 80% polyetheretherketone, 10% diphenyl sulfone and 10% polyphenylene ether.

[0101] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0102] Reaction conditions: mixing temperature 170-285℃, ball milling time 18 minutes, curing temperature 260℃, curing time 3.5 hours, pressure molding pressure 12-15MPa, sintering temperature 155-205℃.

[0103] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0104] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 4

[0105] A ceramic brake pad for new energy vehicles is made of the following components: 33 parts of ceramic material, 48 parts of resin, 8 parts of short fibers, and 12 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 160 ° C, the mixing time is 30 minutes, and then add short fibers, continue mixing for 18 minutes, then add a curing agent, raise the temperature to 320 ° C, continue mixing for 32 minutes, then perform vacuum impurity removal, lower the temperature to 195 ° C, mix for 15 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 25 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 260 ° C and a curing time of 4 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 135 ° C and a stirring time of 22 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 105 ° C, stirred for 48 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 135°C for 6.5 hours to prepare the friction material, then heat the friction material to 155°C to melt it, add the friction material into a molding machine for pressing at a pressure of 20MPa for 4 minutes, then keep the pressure at 3Mpa for 4 minutes, heat the friction material to 215°C, sinter it, and obtain the friction material layer.

[0106] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 5:3:2, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 5:5, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 9:6:15. The ceramic material includes 88% polyetheretherketone, 7% diphenyl sulfone and 5% polyphenylene ether.

[0107] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0108] Reaction conditions: mixing temperature 160-320℃, ball milling time 25 minutes, curing temperature 260℃, curing time 4 hours, pressure molding pressure 20-23MPa, sintering temperature 155-215℃.

[0109] Yield: The theoretical yield is 100%, and the actual yield is 96.5%.

[0110] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 5

[0111] A ceramic brake pad for new energy vehicles is made of the following components: 25 parts of ceramic material, 55 parts of resin, 7 parts of short fibers, and 10 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials by mass, add the resin into a mixer for mixing, the mixing temperature is 155 ° C, the mixing time is 20 minutes, and then add short fibers, continue mixing for 10 minutes, then add a curing agent, raise the temperature to 310 ° C, continue mixing for 25 minutes, then perform vacuum impurity removal, reduce the temperature to 185 ° C, mix for 8 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 20 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 255 ° C and a curing time of 3 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 145 ° C and a stirring time of 25 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 110 ° C, stirred for 45 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 145°C for 5 hours to prepare the friction material, then heat the friction material to 160°C to melt it, add the friction material into a molding machine for pressing at a pressure of 18MPa for 5 minutes, then keep the pressure at 3Mpa for 4 minutes, heat the friction material to 220°C, sinter it, and obtain the friction material layer.

[0112] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 2:2:1, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 4:3, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 8:4:10. The resin is composed of 82% polyetheretherketone, 8% diphenyl sulfone and 10% polyphenylene ether.

[0113] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0114] Reaction conditions: mixing temperature 155-310℃, ball milling time 20 minutes, curing temperature 255℃, curing time 3 hours, pressure molding pressure 18-21MPa, sintering temperature 160-220℃.

[0115] Yield: The theoretical yield is 100%, and the actual yield is 97.5%.

[0116] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 6

[0117] A ceramic brake pad for new energy vehicles is made of the following components: 30 parts of ceramic material, 40 parts of resin, 6 parts of short fibers, and 14 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 165 ° C, the mixing time is 25 minutes, and then add short fibers, continue mixing for 15 minutes, then add a curing agent, raise the temperature to 305 ° C, continue mixing for 20 minutes, then perform vacuum impurity removal, reduce the temperature to 190 ° C, mix for 10 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 25 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 240 ° C and a curing time of 3 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 130° C. for 20 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 100 ° C, stirred for 40 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 130°C for 6 hours to prepare the friction material, then heat the friction material to 170°C to melt it, add the friction material into a molding machine for pressing at a pressure of 15MPa for 4 minutes, then keep the pressure at 2Mpa for 3 minutes, heat the friction material to 230°C, sinter it, and obtain the friction material layer.

[0118] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 3:2:1.5, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:4, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 7:3:10. The resin is composed of 85% polyetheretherketone, 7% diphenyl sulfone and 10% polyphenylene ether.

[0119] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0120] Reaction conditions: mixing temperature 165-305℃, ball milling time 25 minutes, curing temperature 240℃, curing time 3 hours, pressure molding pressure 15-18MPa, sintering temperature 170-230℃.

[0121] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0122] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 7

[0123] A ceramic brake pad for new energy vehicles is made of the following components: 27 parts of ceramic material, 45 parts of resin, 7 parts of short fibers, and 12 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials by mass, add the resin into a mixer for mixing, the mixing temperature is 170 ° C, the mixing time is 28 minutes, and then add short fibers, continue mixing for 12 minutes, then add a curing agent, raise the temperature to 320 ° C, continue mixing for 18 minutes, then perform vacuum impurity removal, lower the temperature to 195 ° C, mix for 8 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 18 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 255 ° C and a curing time of 3.5 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 135 ° C and a stirring time of 25 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 105 ° C, stirred for 35 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 135°C for 5.5 hours to prepare the friction material, then heat the friction material to 165°C to melt it, add the friction material into a molding machine for pressing at a pressure of 16MPa for 4.5 minutes, then keep the pressure at 2.5Mpa for 3.5 minutes, heat the friction material to 225°C, sinter it, and obtain the friction material layer.

[0124] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 4:3:3, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:3, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 8:4:12. The resin is composed of 80% polyetheretherketone, 10% diphenyl sulfone and 10% polyphenylene ether.

[0125] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0126] Reaction conditions: mixing temperature 170-320℃, ball milling time 18 minutes, curing temperature 255℃, curing time 3.5 hours, pressure molding pressure 16-19MPa, sintering temperature 165-225℃.

[0127] Yield: The theoretical yield is 100%, and the actual yield is 97.5%.

[0128] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 8

[0129] A ceramic brake pad for new energy vehicles is made of the following components: 30 parts of ceramic material, 48 parts of resin, 6 parts of short fibers, and 12 parts of filler. The preparation method of the brake pad includes the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 175 ° C, the mixing time is 20 minutes, and then add short fibers, continue mixing for 10 minutes, then add a curing agent, raise the temperature to 300 ° C, continue mixing for 15 minutes, then perform vacuum impurity removal, lower the temperature to 185 ° C, mix for 8 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 25 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 250 ° C and a curing time of 3 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 140° C. for 20 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 110 ° C, stirred for 40 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 140°C for 6 hours to prepare the friction material, then heat the friction material to 160°C to melt it, add the friction material into a molding machine for pressing at a pressure of 18MPa for 5 minutes, then keep the pressure at 3Mpa for 4 minutes, heat the friction material to 220°C, sinter it, and obtain the friction material layer.

[0130] In this embodiment, the number of through holes is at least three, and the three through holes are distributed on the circumference of the inner layer of the lining board, and the angles between adjacent through holes are equal, the distance between adjacent through holes is 11 mm, the diameter of the through hole is 3 mm, and the depth of the through hole is 85% of the thickness of the lining board. The short fiber is composed of nylon fiber and glass fiber in a mass ratio of 2:5, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 6:3:9. The resin is composed of 82% polyetheretherketone, 9% diphenyl sulfone and 9% polyphenylene ether.

[0131] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0132] Reaction conditions: mixing temperature 175-300℃, ball milling time 25 minutes, curing temperature 250℃, curing time 3 hours, pressure molding pressure 18-21MPa, sintering temperature 160-220℃.

[0133] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0134] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 9

[0135] A method for preparing a ceramic brake pad for new energy vehicles is prepared from the following components: 32 parts of ceramic material, 42 parts of resin, 7 parts of short fibers, and 11 parts of fillers.

[0136] The preparation method of this embodiment comprises the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 160 ° C, the mixing time is 25 minutes, and then add short fibers, continue mixing for 15 minutes, then add a curing agent, raise the temperature to 280 ° C, continue mixing for 20 minutes, then perform vacuum impurity removal, reduce the temperature to 190 ° C, mix for 10 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 20 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 230 ° C and a curing time of 3 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 135 ° C and a stirring time of 25 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 100 ° C, stirred for 45 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 135°C for 6 hours to prepare the friction material, then heat the friction material to 150°C to melt it, add the friction material into a molding machine for pressing at a pressure of 15MPa for 3 minutes, then keep the pressure at 2.5Mpa for 3 minutes, heat the friction material to 210°C, sinter it, and obtain the friction material layer.

[0137] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 2:2:1, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:4, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 7:3:8. The resin is composed of 80% polyetheretherketone, 10% diphenyl sulfone and 10% polyphenylene ether.

[0138] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0139] Reaction conditions: mixing temperature 160-280℃, ball milling time 20 minutes, curing temperature 230℃, curing time 3 hours, pressure molding pressure 15-18MPa, sintering temperature 150-210℃.

[0140] Yield: The theoretical yield is 100%, and the actual yield is 97%.

[0141] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 10

[0142] A method for preparing a ceramic brake pad for new energy vehicles is prepared from the following components: 31 parts of ceramic material, 45 parts of resin, 7 parts of short fibers, and 10 parts of fillers.

[0143] The preparation method of this embodiment comprises the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 165 ° C, the mixing time is 20 minutes, and then add short fibers, continue mixing for 10 minutes, then add a curing agent, raise the temperature to 290 ° C, continue mixing for 15 minutes, then perform vacuum impurity removal, lower the temperature to 185 ° C, mix for 8 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 25 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 240 ° C and a curing time of 3.5 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 140° C. for 20 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 105 ° C, stirred for 40 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 140°C for 6 hours to prepare the friction material, then heat the friction material to 155°C to melt it, add the friction material into a molding machine for pressing at a pressure of 18MPa for 4 minutes, then keep the pressure at 3Mpa for 3 minutes, heat the friction material to 215°C, sinter it, and obtain the friction material layer.

[0144] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 3:2:1.5, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 4:3, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 8:4:10. The resin is composed of 82% polyetheretherketone, 8% diphenyl sulfone and 10% polyphenylene ether.

[0145] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0146] Reaction conditions: mixing temperature 165-290℃, ball milling time 25 minutes, curing temperature 240℃, curing time 3.5 hours, pressure molding pressure 18-21MPa, sintering temperature 155-215℃.

[0147] Yield: The theoretical yield is 100%, and the actual yield is 97.5%.

[0148] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Embodiment 11

[0149] A method for preparing a ceramic brake pad for new energy vehicles is prepared from the following components: 29 parts of ceramic material, 46 parts of resin, 6 parts of short fibers, and 10 parts of fillers.

[0150] The preparation method of this embodiment comprises the following steps: S1. Weigh the above-mentioned raw materials by mass, add the resin into a mixer for mixing, the mixing temperature is 158 ° C, the mixing time is 28 minutes, and then add short fibers, continue mixing for 12 minutes, then add a curing agent, raise the temperature to 288 ° C, continue mixing for 18 minutes, then perform vacuum impurity removal, lower the temperature to 182 ° C, mix for 8 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 18 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 242 ° C and a curing time of 3 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, the filler is pulverized in the jet mill to obtain a particle size of 0.01-80 μm, and the short fibers are pulverized in the jet mill to obtain a particle size of 0.005-50 μm, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 128° C. for 25 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 98 ° C, stirred for 38 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 128°C for 5.5 hours to prepare the friction material, then heat the friction material to 152°C to melt it, add the friction material into a molding machine for pressing at a pressure of 16MPa for 4 minutes, then keep the pressure at 2.8Mpa for 3.5 minutes, heat the friction material to 212°C, sinter it, and obtain the friction material layer.

[0151] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 3:2:1.8, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:4, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 7:4:12. The resin is composed of 80% polyetheretherketone, 9% diphenylsulfone and 11% polyphenylene ether.

[0152] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0153] Reaction conditions: mixing temperature 158-288℃, ball milling time 18 minutes, curing temperature 242℃, curing time 3 hours, pressure molding pressure 16-19MPa, sintering temperature 152-212℃.

[0154] Yield: The theoretical yield is 100%, and the actual yield is 97.2%.

[0155] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Example 12

[0156] A method for preparing a ceramic brake pad for new energy vehicles is prepared from the following components: 31 parts of ceramic material, 43 parts of resin, 7 parts of short fibers, and 11 parts of fillers.

[0157] The preparation method of this embodiment comprises the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 162 ° C, the mixing time is 27 minutes, and then short fibers are added, and the mixing is continued for 14 minutes, and then a curing agent is added, the temperature is increased to 295 ° C, and the mixing is continued for 22 minutes, and then a vacuum impurity removal operation is performed, the temperature is reduced to 188 ° C, and the mixing is continued for 9 minutes, and finally the material is discharged to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 22 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 245 ° C and a curing time of 3.2 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively charged into a jet mill for pulverization pretreatment, wherein the filler is pulverized in the jet mill to obtain a particle size of 0.01-90 μm, and the short fibers are pulverized in the jet mill to obtain a particle size of 0.01-60 μm, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 132° C. for 23 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 108 ° C, stirred for 42 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 132°C for 6.2 hours to prepare the friction material, then heat the friction material to 153°C to melt it, add the friction material into a molding machine for pressing at a pressure of 17MPa for 4.2 minutes, then keep the pressure at 3MPa for 3.2 minutes, heat the friction material to 213°C, sinter it, and obtain the friction material layer.

[0158] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 3:2:1.7, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:5, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 6:3:11. The resin is composed of 81% polyetheretherketone, 8% diphenyl sulfone and 11% polyphenylene ether.

[0159] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0160] Reaction conditions: mixing temperature 162-295°C, ball milling time 22 minutes, curing temperature 245°C, curing time 3.2 hours, pressure molding pressure 17-20MPa, sintering temperature 153-213°C.

[0161] Yield: The theoretical yield is 100%, and the actual yield is 97.3%.

[0162] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise. Embodiment 13

[0163] A method for preparing a ceramic brake pad for new energy vehicles is prepared from the following components: 32 parts of ceramic material, 44 parts of resin, 6 parts of short fibers, and 12 parts of fillers.

[0164] The preparation method of this embodiment comprises the following steps: S1. Weigh the above-mentioned raw materials in parts by mass, add the resin into a mixer for mixing, the mixing temperature is 155 ° C, the mixing time is 30 minutes, and then add short fibers, continue mixing for 10 minutes, then add a curing agent, raise the temperature to 305 ° C, continue mixing for 15 minutes, then perform vacuum impurity removal, reduce the temperature to 180 ° C, mix for 8 minutes, and finally discharge the material to obtain a resin mixture A; S2. The phenolic resin was added to a ball mill for ball milling for 20 minutes to obtain a phenolic resin mixture B; S3. The resin mixture A is placed in a friction tablet press and pressed into a block to obtain a ceramic material block, and then the block of ceramic material is cured at a curing temperature of 255 ° C and a curing time of 3 hours; S4. placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5. The short fibers and the filler are respectively loaded into a jet mill for pulverization pretreatment, the filler is pulverized in the jet mill to obtain a particle size of 0.01-100 μm, and the short fibers are pulverized in the jet mill to obtain a particle size of 0.001-60 μm, and then the phenolic resin mixture B obtained in step S2 is added to the filler, and stirred in a mixer at a stirring temperature of 135° C. for 25 minutes to obtain a filler mixture; S6. The phenolic resin mixture B is placed in the mixer, the mixer temperature is adjusted to 100 ° C, stirred for 45 minutes, and cooled to room temperature after stirring to obtain a mixture B; S7. Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 135°C for 6 hours to prepare the friction material, then heat the friction material to 150°C to melt it, add the friction material into a molding machine for pressing at a pressure of 15MPa for 4 minutes, then keep the pressure at 2.5Mpa for 3 minutes, heat the friction material to 210°C, sinter it, and obtain the friction material layer.

[0165] In this embodiment, the filler is composed of diatomaceous earth, mica, and ceramic fiber in a mass ratio of 2:2:1.8, the short fiber is composed of nylon fiber and glass fiber in a mass ratio of 3:4, and the curing agent is composed of epoxy resin, polyetheramine and bisphenol A epoxy resin curing agent in a mass ratio of 7:4:13. The resin is composed of 80% polyetheretherketone, 10% diphenyl sulfone and 10% polyphenylene ether.

[0166] Experimental data: Synthesis method: Follow the above steps S1 to S7.

[0167] Reaction conditions: mixing temperature 155-305℃, ball milling time 20 minutes, curing temperature 255℃, curing time 3 hours, pressure molding pressure 15-18MPa, sintering temperature 150-210℃.

[0168] Yield: The theoretical yield is 100%, and the actual yield is 97.5%.

[0169] Performance test: Through the braking performance test, the ceramic brake pad prepared in this embodiment has a stable friction coefficient and good wear resistance at high temperature, and is suitable for the braking system of new energy vehicles. The experiment shows that the new energy vehicle using this brake pad has excellent performance in high-speed braking, short braking distance and low braking noise.

[0170] Comparative Example 1 This comparative example is a ceramic brake pad for new energy vehicles, and the brake pad is made from the following raw materials in parts by weight: 28 parts of ceramic material, 48 parts of resin, 5 parts of short fibers and 15 parts of fillers; The preparation method of the brake pad comprises the following steps: (a) Mix the resin and an appropriate amount of curing agent, and knead them in an internal mixer at a temperature of 150° C. for 20 minutes; (b) adding the short fibers into an internal mixer and continuing to internally mix for 10 minutes, then raising the temperature to 280° C., adding a curing agent and continuing to internally mix for 15 minutes; (c) performing a vacuum impurity removal operation, lowering the temperature to 175° C., banburying for 5 minutes, and discharging the material to obtain a resin mixture A; (d) adding the phenolic resin into a ball mill and subjecting it to ball milling for 15 minutes to obtain a phenolic resin mixture B; (e) The resin mixture A is pressed into a block, and after solidification, is placed in a mold, fitted with a steel back, and pressure-formed. After a through hole is opened, the block is cooled and taken out to obtain a friction material layer.

[0171] Comparative Example 2 This comparative example is a ceramic brake pad for new energy vehicles, and the brake pad is made from the following raw materials in parts by weight: 35 parts of ceramic material, 40 parts of resin, 5 parts of short fiber and 10 parts of filler; The preparation method of the brake pad comprises the following steps: (a) Mix the resin and an appropriate amount of curing agent, and knead them in an internal mixer at a temperature of 170° C. for 25 minutes; (b) adding the short fibers into an internal mixer and continuing to internally mix for 12 minutes, then raising the temperature to 300° C., adding a curing agent and continuing to internally mix for 20 minutes; (c) performing a vacuum impurity removal operation, lowering the temperature to 190° C., banburying for 10 minutes, and discharging the material to obtain a resin mixture A; (d) adding the phenolic resin into a ball mill and subjecting it to ball milling for 25 minutes to obtain a phenolic resin mixture B; (e) The resin mixture A is pressed into a block, and after solidification, is placed in a mold, fitted with a steel back, and pressure-formed. After a through hole is opened, the block is cooled and taken out to obtain a friction material layer.

[0172] Experimental example The ceramic brake pads for new energy vehicles prepared in Example 10 and Comparative Examples 1 to 2 were obtained respectively; The brake pads were used to perform braking performance tests on new energy vehicles, and the test items included braking distance, braking stability and wear resistance; 30 vehicles were tested for the brake pads of Example 10, 20 vehicles were tested for the brake pads of Comparative Example 1, and 20 vehicles were tested for the brake pads of Comparative Example 2; Test method: On a standard test track, perform emergency braking at the same vehicle speed and record the braking distance and braking stability; On the durability test machine, the wear resistance of the brake pads is tested by simulating actual road conditions; Performance evaluation criteria: Excellent: short braking distance, high braking stability, good wear resistance; Good: Short braking distance, high braking stability and good wear resistance; Average: average braking distance, average braking stability, average wear resistance; Poor: long braking distance, low braking stability and poor wear resistance.

[0173] The statistical performance is shown in Tables 1 to 3: Table 1 Braking distance performance statistics

[0174] Table 2 Braking stability performance statistics

[0175] Table 3 Wear resistance statistics

[0176] From Tables 1 to 3, we can see that: The ceramic brake pads prepared by the technical solution of the present application and the comparative example both perform well in braking performance. Compared with the comparative example, the ceramic brake pads prepared by the technical solution of the present application have significant performance advantages in braking distance, braking stability and wear resistance.

[0177] The above descriptions are only some preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present invention.

Claims

1. A ceramic brake pad for new energy vehicles, characterized in that: The invention comprises a friction material layer and a lining plate, wherein the friction material layer is covered on the lining plate, a through hole is provided on the lining plate, a circular hole is provided on the friction material layer, the circular hole is connected with the through hole, the through hole is filled with a vulcanization layer, the vulcanization layer is located in the circular hole, the friction material layer is made of a ceramic material, the ceramic material comprises a resin, the resin is cured by one or more of polyetheretherketone, diphenylsulfone, polyphenylene ether, polysulfone, polyimide and a curing agent, the components of the friction material layer comprise a filler, the filler comprises one or more of diatomaceous earth, mica, ceramic fiber, carbon fiber, and graphite, the friction material layer further comprises one or more of a binder of phenolic resin, acrylate or carboxymethyl cellulose, the components of the wear-resistant material comprise a short fiber, the short fiber comprises one or more of aramid fiber, nylon fiber, carbon fiber, and glass fiber.

2. The ceramic brake pad for new energy vehicles according to claim 1, characterized in that: The filler is composed of diatomaceous earth, mica and ceramic fiber. In terms of mass percentage, the diatomaceous earth: mica: ceramic fiber = (1-6): (1-3): (1-2).

3. The ceramic brake pad for new energy vehicles according to claim 2, characterized in that: The short fibers are composed of nylon fibers and glass fibers. In terms of mass percentage, the short fibers have a ratio of nylon fibers to glass fibers of (2-5): (2-5).

4. The ceramic brake pad for new energy vehicles according to claim 3, characterized in that: In terms of mass percentage, in the friction material layer: ceramic material: resin: short fiber: filler = (12-33): (30-56): (3-9): (1-4).

5. The ceramic brake pad for new energy vehicles according to claim 4, characterized in that: The resin is composed of the following components by mass percentage: polyetheretherketone: (80-90)% diphenylsulfone: (5-10)% polyphenylene ether: (10-20)%.

6. The ceramic brake pad for new energy vehicles according to claim 3, characterized in that: The curing agent in the friction material component is composed of epoxy resin, polyether amine and bisphenol A epoxy resin curing agent, the structural formula of the polyether amine is: H2N-(CH2CHRCHR)n-NH2, and based on the mass percentage of the curing agent, the added amount of the epoxy resin is 5-10%, the added amount of the polyether amine is 20-30%, and the added amount of the bisphenol A epoxy resin curing agent is 15-35%. The ceramic fiber in the filler is composed of any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber, and silicon carbide fiber.

7. The ceramic brake pad for new energy vehicles according to claim 6, characterized in that: The short fibers are glass fibers, the glass fibers are chopped glass fibers, and the length of the glass fibers is 0.20-0.8 mm.

8. The ceramic brake pad for new energy vehicles according to claim 1, characterized in that: The number of the through holes is at least three, and the three through holes are distributed on the circumference of the inner layer of the lining plate, and the angles between adjacent through holes are equal. The distance between adjacent through holes is 10-12mm, the diameter of the through hole is 2-4mm, and the depth of the through hole is 80-90% of the thickness of the lining plate.

9. A method for preparing a ceramic brake pad for a new energy vehicle, characterized in that: The following steps are involved: S1: Weigh the raw materials in the above mass percentage or weight, add the resin into a mixer for mixing, the mixing temperature is 150-240°C, the mixing time is 5-30min, then add short fibers, continue mixing for 5-20min, then add the curing agent, increase the temperature to 250-350°C, continue mixing for 8-30min, then perform vacuum impurity removal, reduce the temperature to 180-200°C, mix for 5-10min, and finally discharge the materials to obtain a resin mixture A; S2: adding the phenolic resin into a ball mill for ball milling for 10-30 min to obtain a phenolic resin mixture B; S3: placing the resin mixture A into a friction tablet press for pressing into a block to obtain a ceramic material block, and then curing the block ceramic material block at a curing temperature of 200-270° C. and a curing time of 2-5 hours; S4: placing the ceramic material block into a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, the ceramic material block forms a smooth surface on the bottom surface of the mold, a steel back is provided in the mold, a release agent is coated on the inner surface of the mold, the ceramic material block is fitted with the steel back, the mold is placed in a press for pressure molding, a through hole is opened on the upper surface of the steel back during the pressure molding process, the through hole forms a circular hole on the ceramic material block, cooling is performed after the pressure molding is completed, and the friction material layer is obtained after cooling to room temperature and then taken out from the mold; S5: respectively placing the short fibers and the filler into a jet mill for pulverization pretreatment, and then adding the phenolic resin mixture B obtained in step S2 to the filler, stirring in a mixer at a stirring temperature of 120-150° C. for a stirring time of 10-30 min to obtain a filler mixture; S6: placing the phenolic resin mixture B into the mixer, adjusting the temperature of the mixer to 80-120° C., stirring for 30-60 min, and cooling to room temperature after stirring to obtain a mixture B; S7: Add the short fiber and filler mixture into a mixer and stir evenly, then use the mixer to stir the mixture B at a temperature of 120-150°C for 4-8h to prepare the friction material, then heat the friction material to 120-150°C to melt it, add the friction material into a molding machine for pressing at a pressure of 10-25MPa for 2-8min, then keep the pressure at a pressure of 2-5Mpa for 2-5min, heat the friction material to 180-220°C, sinter it, and obtain the friction material layer.

10. The method for preparing a ceramic brake pad for new energy vehicles according to claim 9, characterized in that: In step S3, the ceramic material block is placed in a mold, so that the pressed ceramic material block is fitted with the bottom surface of the mold, and the ceramic material block forms a smooth surface on the bottom surface of the mold. A steel back is provided in the mold, and a release agent is coated on the inner surface of the mold. The ceramic material block is fitted with the steel back, and then it is placed in a press for pressure forming. During the pressure forming process, a through hole is opened on the surface of the steel back, and the through hole forms a circular hole on the ceramic material layer. After the pressure forming is completed, it is cooled, and after cooling to room temperature, it is taken out from the mold to obtain the friction material layer, specifically: In step S4, the pressure forming process is: using a mixer to evenly mix the ceramic material block and the filler mixture, and then placing them into a mold and putting them into a press for one-time pressing, with a pressure of 25-35 MPa and a holding time of 5-15 min; Then, a secondary cold pressing is performed, the pressure is 1-2.5MPa, and the pressure holding time is 5-10min; after cooling, the mold is taken out, and then sanded with sandpaper to form smooth surfaces on the top and bottom surfaces of the ceramic material block; The mold is placed in a press to be molded, the molding pressure is 30-50 MPa, the molding pressure is 2-6 min, and after the molding is completed, it is cooled and taken out from the mold after cooling to room temperature to obtain the friction material layer; In step S6, the sintering temperature is 500-550°C, the sintering time is 5-10 min, and the sintering pressure is 0.1-0.3 MPa.

11. The method for preparing a ceramic brake pad for new energy vehicles according to claim 9 or claim 10, characterized in that: In step S5, when the short fibers and the fillers are pre-crushed in an air flow mill, the particle size of the fillers obtained by crushing in the air flow mill is 0.005-100 μm, and the particle size of the short fibers obtained by crushing in the air flow mill is 0.001-60 μm. In the preparation process of the short fibers, nylon fibers and glass fibers are sequentially fed into the air flow mill for crushing. The nylon fibers are first crushed into particles in the air flow mill, and then the crushed resin is crushed for a second time in the air flow mill. Finally, the crushed nylon fibers and the crushed glass fibers are input into a mixer for stirring, and the stirring temperature is 120-150°C.

12. The method for preparing a ceramic brake pad for new energy vehicles according to claim 9, characterized in that: The curing agent is composed of epoxy resin, polyether amine and bisphenol A epoxy resin curing agent, the structural formula of the polyether amine is H2N-(CH2CHRCHR)n-NH2, the mass percentages of the epoxy resin, polyether amine and bisphenol A epoxy resin curing agent are: the addition amount of the epoxy resin is 5-10%, the addition amount of the polyether amine is 20-30%, and the addition amount of the bisphenol A epoxy resin curing agent is 15-35%, and the ceramic fiber in the filler is composed of any one of silicon oxide fiber, aluminum oxide fiber, zirconium oxide fiber, silicon nitride fiber, and silicon carbide fiber.

13. The method for preparing a ceramic brake pad for new energy vehicles according to claim 12, characterized in that: The filler is composed of diatomaceous earth, mica and ceramic fiber, and by mass percentage, the diatomaceous earth: mica: ceramic fiber = (1-6): (1-3): (1-2); the short fiber is composed of nylon fiber and glass fiber, and by mass percentage, in the short fiber, nylon fiber: glass fiber = (2-5): (2-5); in the preparation process of the short fiber, nylon fiber is used as raw material and is initially crushed in a jet mill to obtain nylon fiber powder, and then the nylon fiber powder is secondary crushed by a jet mill to obtain the short fiber, and the short fiber is a particle of 0.001-60μm.